Independent acquisition of short insertions at the RIR1 site in the spike N‐terminal domain of the SARS‐CoV‐2 BA.2 lineage. Issue 5 (9th August 2022) - Greco, Samuele; Gerdol, Marco
Abstract: Although the major SARS‐CoV‐2 omicron lineages share over 30 non‐synonymous substitutions in the spike glycoprotein, they show several unique mutations that were acquired after their ancestral split. One of the most intriguing mutations associated with BA.1 is the presence of the inserted tripeptide Glu‐Pro‐Glu within the N‐terminal domain, at a site that had previously independently acquired short insertions in several other SARS‐CoV‐2 lineages. Although the functional implications of the small nucleotide sequences found at this insertion hotspot, named RIR1, are still unclear, we have previously hypothesized that they may play a compensatory role in counterbalancing minor fitness deficits associated with other co‐occurring spike non‐synonymous mutations. Here, we show that similar insertion events have independently occurred at RIR1 at least 20 times in early 2022 within the BA.2 lineage, being occasionally associated with significant community transmission. One of these omicron sublineages, characterized by a Ser‐Gly‐Arg insertion in position 212, has been responsible for over 4000 documented COVID‐19 cases worldwide between January and July 2022, for the most part concentrated in Denmark, where it reached a national prevalence close to 4% (10% in the Nordjylland region) in mid‐May. Although the concurrent spread of the BA.2.12.1, BA.4 and BA.5 lineages led to the rapid decline of this BA.2 sublineage, the independent acquisition of several other RIR1 insertions on a BA.2 genomic background suggests that these events may provide a slight fitness advantage. Therefore, they should be carefully monitored in the upcoming months in other emerging omicron‐related lineages, including BA.5.